Impact of internal mammary artery perforator propeller flaps combined with radiotherapy in the treatment of large chest keloids: Our experience - Zhao, Jianfang; Xie, Kun; Qin, Shangbin; He, Rui; Jiang, Shan; Qi, Xin; Wen, Bing (Frontiers in Surgery, 2023)
ABSTRACT Background Keloids are benign skin hyperplasias but have a tumor-like appearance. Clinical management of keloids remains challenging. Aims We retrospectively evaluated the safety and efficacy of internal mammary artery perforator propeller flaps combined with timely radiotherapy in the treatment of large chest keloids. Methods From June 2017 to May 2020, 25 patients with large chest keloids (average size 4.82±2.53 x 9.04±4.86 cm) who received both radiotherapy and internal mammary artery perforator flaps transplantation in our department were included. After surgical removal of the keloids, various propeller flaps based on the unilateral internal mammary artery were designed and applied to repair the defects. Timely and full-dose radiotherapy was performed for these patients after the operation. Results After keloid resection, the dimensions of the defect area were 3-15 cm x4-25 cm, and the sizes of the flaps were 3-16 cm x4-27 cm. For all 25 patients, the flaps survived, and the incisions healed in one stage. During the follow-up (median 18 months), no local recurrence was observed, and the itching and pain symptoms in the scar area were significantly relieved. Both physicians and patients were satisfied with the results. Conclusions The application of internal mammary artery perforator propeller flaps combined with radiotherapy in the treatment of chest keloids can effectively reduce the recurrence of keloids and relieve the related symptoms. It also has advantages including minimized donor site damage, short operation time and speedy postoperative recovery, suggesting its great clinical value.